A Simulation Study of Cooperative Communications over HF Channels - Hakeem, Mohammed Jameel (University of Waterloo, 2008)
The High Frequency (HF) band lies within 2-30 MHz of the electromagnetic spectrum. In this part of the spectrum, propagation via direct wave, surface wave, and ionospheric refraction mechanisms provides means of communications from line-of-sight to beyond-line-of-sight ranges. The characteristics of ionospheric channel impose fundamental limitations on the performance of HF communication systems. The major impairment is fading which results in random fluctuations in the received signal level and affects the instantaneous signal-to-noise ratio. This requires the deployment of powerful diversity techniques to mitigate the degrading effects of fading on the performance. The range of wavelengths in HF band unfortunately restricts the use of spatial diversity (i.e., deployment of multiple antennas) for most practical purposes. This thesis focuses on an alternative method to exploit the spatial dimension of the HF channel. Specifically, we aim to extract distributed spatial diversity through relay-assisted transmission. Towards this main goal, we consider multi-carrier HF communication and investigate the performance of cooperative OFDM over HF channels.
Keywords: cooperative communication; HF channel; Electrical and Computer Engineering